RISK-BASED STAKEHOLDER MANAGEMENT MODEL FOR SELF-MANAGED ELEMENTARY SCHOOL REVITALIZATION PROGRAMS - Andita Citra Puspita; Rully Andhika Karim (jfpublisher, 2026)
Indonesia's elementary school infrastructure faces significant challenges, with approximately 174,000 educational units experiencing moderate to severe classroom damage. The 2025 Elementary School Revitalization Program, implementing a self-managed mechanism with direct fund disbursement to schools, represents a policy innovation requiring effective stakeholder coordination and risk management. This research develops a risk-based stakeholder management model for the program's implementation. The study employs a mixed-method approach combining document analysis, stakeholder surveys, and expert validation following Project Management Body of Knowledge (PMBOK) standards. Data were collected from school principals, School Development Committees (P2SP), education offices, and technical consultants across multiple implementation sites. Results reveal seventeen key stakeholders categorized through power-interest analysis, with five identified as key players requiring intensive engagement. Critical communication pathways exist between schools, district education offices, and central directorates. Twenty-three dominant risks were identified, primarily administrative and communication-related rather than technical. The developed model integrates stakeholder mapping, communication mechanisms, and risk mitigation strategies into a comprehensive engagement framework. This research contributes a practical tool for enhancing program transparency, accountability, and effectiveness in self-managed educational infrastructure projects.